The Effect of Viral Marketing and Online Customer Reviews on Instagram on Purchase Decisions for Mixue Ice Cream in Surabaya - Syamsya, Syabania Qowi Nur; Purwanto, Sugeng (Profesional Muda Cendekia Publishing, 2023)
A new ice cream brand from China called “Mixue” appeared in Indonesia recently and made people queue just to taste the ice cream product, even though Mixue is not the first choice of ice cream brand in Indonesia. The researcher wanted to find out the impact of viral marketing and online customer reviews on Instagram on the purchase decision of Mixue ice cream in Surabaya. This study used quantitative methods, with the research subjects being Mixue ice cream consumers in Surabaya and Instagram users. This study involved the participation of 98 people using the non-probability sampling method and purposive sampling as the technique. To collect data, researchers distributed questionnaires online with a Likert Scale. The data would be analyzed using the Partial Least Squares (PLS) method. The results showed that viral marketing had a substantial impact on Mixue ice cream purchase decisions in Surabaya, and online customer reviews had a large impact on Mixue ice cream purchase decisions in Surabaya.